Peningkatan Kesadaran Wirausahawan melalui Pelatihan Hak Kekayaan Intelektual dan Penerapan Undang-Undang Hak Cipta: Enhancing Entrepreneur Awareness through Intellectual Property Rights Training and Copyright Law Implementation - Marwiyah, Marwiyah; Jauhari, Jauhari (PengabdianMu: Jurnal Ilmiah Pengabdian kepada Masyarakat, 2024)
Intellectual Property Rights (IPR) play a crucial role in modern business, especially for entrepreneurs who rely on innovation and creativity to remain competitive. IPR encompasses copyrights, patents, trademarks, and industrial designs that protect intellectual works and grant exclusive rights to their owners. However, awareness and understanding of the significance of IPR still pose significant challenges. A lack of knowledge about IPR can lead to economic losses due to copyright infringement and piracy, which in turn impedes business growth and innovation. Enhancing awareness and the implementation of copyright laws through training is an effective strategy to protect entrepreneurs' creative assets. This training provides an in-depth understanding of the importance of IPR, the registration process, and methods for protecting and enforcing copyrights. Conducted online via Zoom Meeting, the program involves preparation, execution, and evaluation phases. Results show enthusiastic and active participation from 70 attendees, including students, entrepreneurs, SME operators, and the general public. Data indicate that the training is most popular among individuals aged 20-25 and students, who constitute 76% of the participants. Evaluations demonstrate a significant increase in participants' knowledge, aiding them in protecting their creative assets, fostering innovation, and reducing legal conflicts related to copyrights, thus supporting a healthier business ecosystem.